DEVELOPING A MATHEMATICS EBOOK BASED FLASH FOR CLASS VIII LINEAR AND EQUATION SYSTEM OF TWO VARIABLES MATERIAL - Riska Zunanto; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
Flash-based math ebook development for student of 8th grade in a system of linear equation in two variables material be set in learning of the lack of development of a variety of electronic learning media of mathematics as well as lack of utilization of information and communication technology for learning in SMP Muhammadiyah Banguntapan and SMP Muhammadiyah Boarding School Pleret. This study aims to develop a flash-based math ebook for a student of 8th grade in a system of linear equation in two variables material and know the properness of the ebook. The method used in this research is Research and Development (R & D) by using the ADDIE modelÂ (Analysis, Design, Development, Implementation, and Evaluation). The subject of this study are two media experts, two math experts, 38 students of 8th grade of SMP Muhammadiyah Banguntapan, 12 students of 8th grade of Al-Qadar Banguntapan tutoring class and 31 students of 8th grade SMP Muhammadiyah Boarding School Pleret. This research used the non-test technique. While the research instrument used was questionnaires assessment for media experts, material experts, and the response of students who had evaluated before, through instrument test, validity test, and form. The technique of data analysis is qualitative and quantitative analysis to describe the ideas and analyzes the assessment result of material experts, media experts, and responses of a student to the book. Â Result of the study and development show that math ebook development include in good category based on questionnaire Assesment by material expert with average score 62,00 from a maximum score of ideal 75. Results of questionnaire assessment by media expert include in good category based on questionnaire Assesment by material expert with average score 83,50 from maximum score of ideal 100. Whereas results of questionnaire assessment by student responses on product trials in a small class and large class include in a good category with an average score of 33.62 from a maximum score of ideal 40. The result of the study shows that flash-based math ebook development for the student of 8th grade in the system of linear equation in two variables material proper to used in the learning process.